2022
DOI: 10.9745/ghsp-d-22-00228
|View full text |Cite
|
Sign up to set email alerts
|

What Underlies State Government Performance in Scaling Family Planning Programming? A Study of The Challenge Initiative State Partnerships in Nigeria

Abstract: Strong external champions-both traditional and religious leaders but also media-savvy policy advocates-were a key component of a successful scaling experience by building public understanding and support for FP use and holding government leaders accountable for its provision. n Skilled and empowered state program officers, with support from internal government champions at the highest political but also agency leadership levels, spearheaded the introduction and implementation of the interventions and guided th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Ishola et al 13 describe a mixed-methods comparative case study to determine facilitators and barriers to subnational (state-level) adoption, implementation, and scale-up of high-impact FP/AYSRH interventions. The authors found that among 3 Nigerian states that had received substantive coaching support and financial investment, 2 states were higher performing and one lower performing, as determined by growth in FP client service volume over 24 months of implementation.…”
Section: Scaling and Sustainability Of Family Planning Interventionsmentioning
confidence: 99%
“…Ishola et al 13 describe a mixed-methods comparative case study to determine facilitators and barriers to subnational (state-level) adoption, implementation, and scale-up of high-impact FP/AYSRH interventions. The authors found that among 3 Nigerian states that had received substantive coaching support and financial investment, 2 states were higher performing and one lower performing, as determined by growth in FP client service volume over 24 months of implementation.…”
Section: Scaling and Sustainability Of Family Planning Interventionsmentioning
confidence: 99%